Deliberative layering: Explaining diverse interest mobilization across the European Parliament's Policy Cycle. Issue 1 (5th April 2020) - Coen, David; Lehmann, Wilhelm; Katsaitis, Alexander
Abstract: Drawing from work on deliberation and information‐access, this paper conceptually frames why and when different types of interests mobilize across the parliamentary policy cycle. We posit that each policy stage holds its own deliberative purpose and logic, leading to a variation in the type and volume of information demanded. The legitimacy of the expertise interest groups provide is affected by their organizational characteristics. To ensure the smooth flow of the policy process, members of parliament encourage groups that legitimately hold relevant information to mobilize at each policy stage, while lobbyists choose to mobilize when their expertise allows them to better influence policy‐makers' debates. We test our argument in the context of the European Parliament, following a unique survey of the 8th legislature (2014–2019). The responses lend support to our model. In a policy process that contains various stages of deliberation, different organizations hold an information‐expertise key that gives them access at different stages. Significantly, less studied groups, such as think tanks and consultancies, mobilize well ahead of others in the cycle's initial phases; while lobbyists representing public constituencies dominate in the final stages. The paper contributes to broader theoretical discussions on pluralism, bias, and deliberation in policy‐making.